Translation and Identity: Social Trajectories of the Translators of Hebrew Literature in French - Sapiro, Gisèle (TTR)

(untitled) (Association canadienne de traductologie, 2013)
This paper focuses on the relation between translation and identity through the case of translators from Modern Hebrew literature into French. The conditions of acquisition of linguistic skills and the paths that lead to the translational practice are analysed on the basis of a study of the social properties and trajectories of the translators, which reveals the population’s double historical process of specialization and of femininization. The way translators represent their activity to themselves, as expressed during in-depth interviews, is then placed in the context of the translators’ trajectories and habitus, following Daniel Simeoni’s suggestion. The question of translation’s role in the construction of individual and collective identity is thereby raised.